A finite element model of solar heating system with underground storage - Ucar, A.; Inalli, A. (Elsevier France-Editions Scientifiques Medicales Elsevier, 2008)
In this study, the performance of a solar heating system with seasonal storage is evaluated using finite element method. The time-dependent heat transfer problem between storage and the surrounding ground is solved by using a computer program in MATLAB and the transient temperature distribution in ground and transient temperature of water in the storage are calculated. The effects of storage volume and solar collector area on annual average temperature distribution in the round surrounding storage are investigated. It is observed that the temperature of water in the storage increases with increase of the solar collector area. It was found that the water temperature for storage surrounded with sand ground was higher than the other ground types. (C) 2007 Elsevier Masson SAS. All rights reserved.
Keywords: Solar energy; Seasonal storage; Finite element